Restart - Korman, Gordon (New York, NY : Scholastic Press, 2017)
Chase does not remember falling off the roof, in fact he does not remember anything about himself, and when he gets back to middle school he begins to learn who he was through the reactions of the other kids--trouble is, he really is not sure he likes the Chase that is being revealed, but can he take the opportunity amnesia has provided and restart his life?
Keywords: Amnesia -- Juvenile fiction; Memory -- Juvenile fiction; Bullies -- Juvenile fiction; Self-perception -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Amnesia -- Fiction; Memory -- Fiction; Bullying -- Fiction; Self-perception -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction